A sinagoga desenganada: um tratado antijudaico no Brasil do começo do século XVIII - Feitler, Bruno (Revista de História, 2003)
Sinagoga Desenganada, by the Jesuit Giovanni Pietro Pinamonti, is published in Lisbon in 1720. This article deals with the context of translation and publication of this original work because of those who published it: the Jesuit Andreoni, and the archbishop D. Sebastião Monteiro da Vide. We can see that in Brazil of the 18th century, the fear of the Jewish heresy was a reality, and that in order to achieve peace and well-being, one had to fight against it.